1980
DOI: 10.1111/j.1432-1033.1980.tb04499.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse‐Fluorometry Study on Actin and Heavy Meromyosin Using F‐Actin Labelled with N‐(1‐Pyrene)maleimide

Abstract: The single‐photoelectron counting technique was used for measurement of the fluorescence decay kinetics of N‐(1‐pyrene)maleimide conjugated to the fast reactive cysteine of actin. The fluorescence decay curve of the labelled G‐actin could not be described by a single‐exponential function but by a double‐exponential function. Polymerization of actin was accompanied by significant changes in the decay parameters of the two decay components. We found that the ionic strength, which plays an important role in the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…In all cases, the excitation wavelength (λ x ) 1 was set with a monochromator, and the emission wavelength (λ m ) was set either with a monochromator (conventional fluorometer) or with long-pass filters (stopped-flow). The following excitation and emission wavelengths were used to monitor changes in pyrene fluorescence: λ x = 344 nm, λ m = 366 nm (12); λ x = 365 nm, λ m = 385 nm (13); and λ x = 365 nm, λ m = 407 nm (15,20). Each method gave the same rate of polymerization although the amplitude of the signal and the extent to which scattered light contributed to the final signal varied with each case.…”
Section: Polymerization Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In all cases, the excitation wavelength (λ x ) 1 was set with a monochromator, and the emission wavelength (λ m ) was set either with a monochromator (conventional fluorometer) or with long-pass filters (stopped-flow). The following excitation and emission wavelengths were used to monitor changes in pyrene fluorescence: λ x = 344 nm, λ m = 366 nm (12); λ x = 365 nm, λ m = 385 nm (13); and λ x = 365 nm, λ m = 407 nm (15,20). Each method gave the same rate of polymerization although the amplitude of the signal and the extent to which scattered light contributed to the final signal varied with each case.…”
Section: Polymerization Assaysmentioning
confidence: 99%
“…Pyrene-labeled actin was prepared by reacting F-actin with N- (1-pyrenyl)iodoacetamide (Molecular Probes) using the method of Kouyama and Mihashi (15). The actin was depolymerized by exhaustive dialysis, clarified by centrifugation, and then purified by gel-filtration chromatography on a Sephacryl S-200 column.…”
Section: Protein Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Signals that are sensitive to local conformational changes were usually reported to give a unidirectional response which was a linear function of the fraction of actin monomers bound [15,31,62,[72][73][74], although cooperative (non-linear) effects were also reported [6, 611 and other authors observed a biphasic change in ultraviolet absorption [75] and fluorescence intensity of static fluorescence anisotropy of etheno-ADP in F-actin [31,76]. Probes reporting the rotational mobility of F-actin give a cooperative response [4,6,11,12,15,771 (and this work), usually unidirectional, but a biphasic response was observed in the quasi-elastic light-scattering [4, 61.…”
Section: Discussionmentioning
confidence: 99%
“…Actin was purified from rabbit skeletal muscle as described previously (39,40). Monomeric actin was purified by gel filtration chromatography using S-300 resin to remove oligomers.…”
Section: Methodsmentioning
confidence: 99%